Reclassification of Bracon mendocinus , a gall‐associated doryctine wasp, and description of a new closely related species of Allorhogas (Hymenoptera: Braconidae) - Martinez, Juan Jose (2008)
One of the first reported gall-associated braconids, from 1910, Bracon mendocinus Kieffer & Jörgensen, is removed from the subfamily Braconinae and transferred to the doryctine genus Allorhogas, A. mendocinus (Kieffer & Jörgensen) comb. nov. A new species morphologically similar to A. mendocinus, A. joergenseni Martinez & Zaldivar-Riverón sp. nov., is also described. Additionally a neotype is designated for B. mendocinus Kieffer & Jörgensen. We base our conclusions on the morphological examination of recently collected specimens from central Argentina associated with galls on Lycium chilense (Solanaceae), as well as on the DNA variation at 28S rRNA and COI mtDNA genes.